The Influence of Locally Generated Revenue, Public Allocation Funds and Specific To Financial Performance of The Region in The City/Regency Government in Aceh Province - Zainal Putra (AFEBI Economic and Finance Review, 2016)
The purpose of this research are: (1). To know how the condition of region own source revenue, the general allocation fund, special allocation fund and regional financial performance , (2). To find out the influence of region own source revenue, the general allocation fund, special allocation fund to the region financial performance, (3). To know the influence of region own source revenue to the region financial performance, (4). To find out the influence of the general allocation fund to the region financial performance, (5). to know the effect of the special allocation fund toward region financial performance. The data used in this research is a secondary data obtained from the office of BPK RI Aceh province Representative. The data collected in the form of pooling data in period of 2008-2012. The entire population in this research are sampled as many as 23 regencies / cities in Aceh province. In analyzing the data using multiple linear regression models. The results showed that: (1). Regencies / cities in Aceh province the category of of region finance ability is “very less" and the category of Region Finance Independence is "very low" with a pattern of "instructive" relationship, (2). The financial performance of the region show a decreasing trend in the span of 2008-2012 , (3). The variable of region own source revenue, general allocation fund, special allocation fund simultaneously influential and significant to the variable of regional financial performance , (4). Partially only variable of general allocation fund and variable of special allocation fund that influence and significant toward the variable of regional financial performance, whereas the variable of region own source revenue does not influence significantly to the variable of regional financial performance.JEL Classification: H20, H50, P50Key words: The General Allocation Fund, The Region Own Source Revenue, The Regional Financial Performance, The Special Allocation Fund